Henry Clay Frick and the Museum of Fine Arts, Boston: the blockbuster exhibition of 1910. (29th January 2021) - Scott, Nancy
Abstract: November 1909 the Museum of Fine Arts in Boston inaugurated its second home, in a grand neoclassical-style building, and premiered innovative exhibition designs based on research in European museums. Henry Clay Frick soon displayed fifty of his paintings in the museum's Old Masters gallery – the only occasion in his lifetime that he would lend such an expansive selection of paintings from his collection to a civic museum. Archival discoveries offer a reconstruction of the historic moment that brought together the new Boston museum, Frick's paintings and an engaged public, shaping Frick's vision of his collection's legacy.